Clinical and microbiological evaluation of one-stage full-mouth disinfection: a short-term study - José Roberto Cortelli; Marcos Vinicius Moreira de Castro; Rodrigo Dalla Pria Balejo; Camila Oliveira de Alencar; Antonio Carlos Gargioni Filho; Sheila Cavalca Cortelli; Fernando Oliveira Costa
INTRODUCTION: Patients seem to adhere better to short-term periodontal treatment schemes. Besides, time-reduced treatments are more cost-effective. However, the degree of benefits related to this type of treatment still requires additional investigations. AIM: The present short-term study evaluated clinical and microbiological outcomes, from baseline to 3-months, of chronic periodontitis subjects treated by the one-stage full-mouth disinfection protocol. MATERIAL AND METHOD: Sixteen chronic periodontitis subjects (mean-age 49.87 ± 8.22) who met inclusion/exclusion criteria were included. A calibrated examiner measured whole-mouth plaque and gingival indices, periodontal pocket depth and clinical attachment level at baseline and at 3-months. Subgingival samples were also collected from the 5 most diseased periodontal sites to determine total bacterial load and levels of P. gingivalis and S. oralis by real time qPCR. Periodontal treatment consisted of full-mouth manual debridement plus wide intraoral use of chlorhexidine in gel and solution. Additionally, after debridement, individuals rinsed 0.12% chlorhexidine at home twice a day for the following 2 months. Data monitored were compared by paired Student-t test (p<0.05). RESULT: Statistical analysis revealed that, in general, one-stage full-mouth disinfection treatment provided significant clinical and microbiological improvements at 3-months. Total bacterial load showed one of the most pronounced reductions from baseline to 3-months (p=0.0001). Also, subgingival levels P. gingivalis and S. oralis reduced overtime. CONCLUSION: After a short period of monitoring, chronic periodontitis subjects showed clinical and microbial improvements following one-stage full-mouth disinfection treatment.